Warunki prowadzenia działalności gospodarczej w opinii jeleniogórskich przedsiębiorstw - wyniki badań ankietowych z 2007 r. na tle sondażu z 2005 r. - Basta, Kamil; Curyło, Marta; Heleniak, Aleksandra; Maćkula, Jarosław (Conditions for Conducting Business Activity According to Business Entities in Jelenia Góra - 2007 Survey Results Against 2005 Survey Results, 2008)
This paper is a report by Pro Future - Students' Scientific Group of Economy and Public Administration and it is a summary of surveys conducted among business entities in Jelenia Góra. The survey was aimed at identification and assessment of the conditions for business activity and recognition of progressing changes in the local business atmosphere between 2005 and 2007. Survey respondents expressed their opinions about technical infrastructure, natural conditions, local business policies, the local real estate market, the local labour market, the institutional business environment, as well as problems and perspectives for entrepreneurs. Against the 2005 survey results, the feedback seems to indicate that business activity conditions in Jelenia Góra have deteriorated. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 419-430